Handball Sports Medicine Basic Science, Injury Management and Return to Sport (Springer Berlin Heidelberg, 2018)
This book is designed to help improve the medical care of athletes across the world who play team handball - including not only handball itself but also such sports as beach volleyball and mini-handball. It provides concise practical information on the nature of frequently encountered injuries, the management of these injuries, injury prevention, and rehabilitation following treatment. Individual sections also focus on physiologic, endocrinologic, biomechanical, and nutritional aspects; special considerations in particular groups of players; and psychological issues. The medical needs of a handball team are explained, and guidance offered on preparticipation assessment and screening. All of the authors are leaders in their field. Their excellent teamwork ensures that the book, published in collaboration with ESSKA, will represent a superb, comprehensive educational resource. It will meet the needs of both handball medical caregivers and handball personnel, providing readily accessible answers to a wide range of medical questions and facilitating effective collaboration among the various professionals involved in team handball.